Exploring the Application of the Borg & Gall Development Model in Science Education: A Review of Literature - Ryya Aulia Assirri; I Putu Artayasa; Nisa Hidayatullah; Riska Dia Sapitri; Rizka Sofia Irawan; Satutik Rahayu (Indonesian Journal of Innovation in Education Research, 2026)
The Borg & Gall Research and Development (R&D) model is a methodological framework widely applied in science learning development because it focuses on solving learning problems through empirical data-based evaluation and revision. This study aims to describe and analyze trends in the application of the Borg & Gall model in science learning development, including variations and modifications in stages, evaluation strategies, development outcomes, and challenges reported in previous research. The method used was a literature review using the SPIDER (Sample, Phenomenon of Interest, Design, Evaluation, Research type) approach. A systematic literature search was conducted through Google Scholar, ERIC, and ScienceDirect databases. The results indicate that most studies do not fully implement the Borg & Gall stages, but instead simplify or integrate them with other instructional design models to accommodate the learning context, time constraints, and resource constraints. The dominant evaluation strategies include expert validation, phased field trials, and measuring effectiveness through pre-test and post-test designs. In general, the developed science learning products were declared valid, practical, and effective, although they still face challenges in terms of time, cost, technical competence, and generalizability of the results